(untitled) (Global Journal of Medical Research, 2023)
Abstract The article offers holistic approach to pain - definition of acute and chronic pain and how they need to be treated Then the article explains why changes in the atmospheric pressure and microwave radiation increase the level of pain The influence of our 4G and 5G technologies on our body its health and its levels of pain is also discussed Discussed is also the necessity to have safety regulations for the admissible safe electromagnetic radiation including microwave radiation in the way we have limits for safe ionization radiation Since we all have electromagnetic field which rules and regulates everything in the body the influence of external electromagnetic fields including microwaves is substantial and should always be considered Key Words pain acute pain chronic pain pain and atmospheric pressure pain and microwaves pain and 4G 5G technologies necessity of new regulations